Internally Displace Persons and Informal Citizenship: Sampang Shiites’ Struggle after Sectarian Violence - Fiqh Vredian Aulia Ali (Peradaban Journal of Religion and Society, 2022)
After a sectarian attack on the Shia community in Sampang, Indonesia, they live in refugee camps. Even though the refugees have now returned, the reconciliation efforts took quite a long time. The Shia community had to live in refugee camps for about ten years. This paper argues that the clientelistic structure is the main obstacle to repatriation. Amid social and economic marginalization and the limited role of the government in fulfilling their basic rights in the refugee camps, the Shia of Sampang can still hold on to fulfill their citizenship and hope to return home through informal networks and mechanisms. This article shows that although with the help of various parties, the Sampang Shia community can gradually gain legal status, political participation, and (limited) economic rights as citizens, it is still difficult for them to regain their membership in Sampang socially and culturally.